Strategies to resistance to bacterial wilt disease of banana through genetic engineering - Tripathi, L.; Tripathi, J.N.; Tushemereirwe, Wilberforce K. (2004)
The livelihoods of millions of Ugandan farmers have been threatened by current outbreak of a banana bacterial wilt disease caused by Xanthomonas campestris pv. musacearum, which is very destructive and rapidly spreading in Uganda. Bananas are the highest value staple food and source of income for millions of people in this region. Economic impact of the disease is clear as a result of widespread destruction of banana, pre-harvest rotting of fruits, and a lack of farmers' ability to grow bananas in disease endemic areas. The disease attacks all varieties of banana, including East African Highland Bananas (EAHBs). No banana germplasm with bacterial wilt resistance has been identified. The transgenic approach shows potential for the genetic improvement of the crop using a wide set of transgenes currently available which may confer bacterial resistance. This article discusses the potential strategies to develop transgenic banana plants resistant to bacterial wilt disease.